Visimuka: Video Tour Situs Muara Kaman based on Instagram for Class X Students of SMA Negeri 1 Tenggarong Seberang, Kutai Kartanegara Regency - Rani, Rani Tri Wahyuni; Khakim, Moch. Nurfahrul Lukmanul (Yupa: Historical Studies Journal, 2024)
This development research was carried out based on observations of problems and potentials that exist in SMA Negeri 1 Tenggarong Seberang. The problem found is the lack of innovation in history learning media and the low knowledge of students about the Muara Kaman Site cultural heritage of the Kutai Kingdom, for this reason, learning media innovations are needed that can overcome these problems. Several potential schools can support the development of digital learning media, such as the Video Tour Situs Muara Kaman (Visimuka). Visimuka is a learning media in the form of short videos taken directly at the Muara Kaman Site, then edited using the InShot application, and uploaded on Instagram social media. The research uses the ADDIE model which has five steps, namely Analyze (analyze), Design (design), Development (develop), Implement (implement), and Evaluate (evaluate). Visimuka learning media is a digital media that has gone through a validation test with very valid media results and a product feasibility test with the results of the media very feasible to use for history learning.